Habitat and landscape effects on fauna in oil palm plantations highlight implications for biodiversity, yield, and plantation management - Caitlin S. Willis; Erin K. Wills; Reza Azmi; Catherine M. Yule; Ben L. Gilby (Agriculture, Ecosystems & Environment, 2026)

Flexural behavior of rectangular CFDST beams with intermittently-welded plate stiffeners and recycled-lightweight concrete - Amjad Ali K. Sharba; Mohd Reza Azmi; Mohd Yazmil Md. Yatim (Innovative Infrastructure Solutions, 2026)

Forensic characterization and identification of mystery white blobs spilled on Newfoundland beaches - Chun Yang; Zeyu Yang; Michael Murphy; Wenxing Kuang; Michael Goldthorp; Pervez Azmi; Claire Courtemanche; Mohammad Shihab Reza; Daniel Demczuk; Taisia Kostyleva; Bruce Hollebone; Patrick Lambert; et al. (Journal of Hazardous Materials, 2026)

Habitat structure and landscape context influence vocalising vertebrates in oil palm plantations - Erin K. Wills; Caitlin S. Willis; Reza Azmi; Dominique A. Potvin; Baizul Hafsyam Badli-Sham; John Howes; Catherine M. Yule; Ben L. Gilby (Biodiversity and Conservation, 2026)
As global food demand rises with population growth, much of the expected land conversion to agriculture is projected to occur in tropical biodiversity hotspots. Balancing food production and biodiversity conservation requires managing agricultural landscapes to serve both goals. To support this, we examined how animal distribution in an oil palm plantation is influenced by landscape context and habitat structure. The study was conducted in Johor, Malaysia, a region dominated by oil palm agriculture. Passive acoustic recorders were deployed across 35 sites within a 1160-hectare oil palm plantation, encompassing a range of yield levels, and distances to natural features. Recordings were collected periodically during the inter-monsoonal period, April-May 2025, targeting peak seasonal and circadian vocal activity of birds and anurans, and analysed using BirdNET and manual spectrogram inspection to identify birds, anurans, and mammals. A total of 89 vertebrate species (75 birds, 12 anurans, 2 mammals) were detected, including several threatened species. Species richness was greatest at sites with taller canopies, lower frond cover, and closer proximity to water and forests, highlighting the importance of maintaining structural complexity and connectivity to maximise biodiversity within plantations. Exploratory analysis found no significant relationship between bird richness, including frugivores, and palm oil yield, thereby suggesting limited short-term effects, though extended studies are required to evaluate longer-term biodiversity influences on production. To enhance biodiversity, we recommend replanting native trees on low-yield blocks, enhancing vertical structure with tree islands, and maintaining clean waterways, while keeping frond stacking to

Experiences and insights of thalassaemia carriers from an indigenous community in Sabah, Malaysia - Norita Hussein; Yew Kong Lee; Syahirah Mohamed Reza; Primus John; Anisah Azmi; Nadeem Qureshi; Chirk Jenn Ng (Journal of Community Genetics, 2025)

Protective effects of feed additives on broiler chickens exposed to aflatoxins-contaminated feed: a systematic review and meta-analysis - Reza Pratama Putra; Dian Astuti; Adib Norma Respati; Niati Ningsih; Triswanto; Aan Andri Yano; Besse Mahbuba We Tenri Gading; Anuraga Jayanegara; Mohammad Miftakhus Sholikin; Hasliza Abu Hassim; Amirul Faiz Mohd Azmi; Danung Nur Adli; et al. (Veterinary Research Communications, 2024)

Genotype–phenotype correlation in contactin-associated protein-like 2 (CNTNAP-2) developmental disorder - Gianluca D’Onofrio; Andrea Accogli; Mariasavina Severino; Haluk Caliskan; Tomislav Kokotović; Antonela Blazekovic; Kristina Gotovac Jercic; Silvana Markovic; Tamara Zigman; Krnjak Goran; Nina Barišić; Vlasta Duranovic; et al. (Human Genetics, 2023)
Contactin-associated protein-like 2 ( CNTNAP2 ) gene encodes for CASPR2, a presynaptic type 1 transmembrane protein, involved in cell–cell adhesion and synaptic interactions. Biallelic CNTNAP2 loss has been associated with “Pitt-Hopkins-like syndrome-1” (MIM#610042), while the pathogenic role of heterozygous variants remains controversial. We report 22 novel patients harboring mono- ( n = 2) and bi-allelic ( n = 20) CNTNAP2 variants and carried out a literature review to characterize the genotype–phenotype correlation. Patients (M:F 14:8) were aged between 3 and 19 years and affected by global developmental delay (GDD) ( n = 21), moderate to profound intellectual disability ( n = 17) and epilepsy ( n = 21). Seizures mainly started in the first two years of life (median 22.5 months). Antiseizure medications were successful in controlling the seizures in about two-thirds of the patients. Autism spectrum disorder (ASD) and/or other neuropsychiatric comorbidities were present in nine patients (40.9%). Nonspecific midline brain anomalies were noted in most patients while focal signal abnormalities in the temporal lobes were noted in three subjects. Genotype–phenotype correlation was performed by also including 50 previously published patients (15 mono- and 35 bi-allelic variants). Overall, GDD ( p < 0.0001), epilepsy ( p < 0.0001), hyporeflexia ( p = 0.012), ASD ( p = 0.009), language impairment ( p = 0.020) and severe cognitive impairment ( p = 0.031) were significantly associated with the presence of biallelic versus monoallelic variants. We have defined the main features associated with biallelic CNTNAP2 variants, as severe cognitive impairment, epilepsy and behavioral abnormalities. We propose CASPR2-deficiency neurodevelopmental disorder as an exclusively recessive disease while the contribution of heterozygous variants is less likely to follow an autosomal dominant inheritance pattern.

Smallholder oil palm plantation sustainability assessment using multi-criteria analysis and unmanned aerial vehicles - Yong Bin Wong; Chris Gibbins; Badrul Azhar; Su Shen Phan; Paul Scholefield; Reza Azmi; Alex M. Lechner (Environmental Monitoring and Assessment, 2023)
Oil palm agriculture has caused extensive land cover and land use changes that have adversely affected tropical landscapes and ecosystems. However, monitoring and assessment of oil palm plantation areas to support sustainable management is costly and labour-intensive. This study used an unmanned aerial vehicles (UAV) to map smallholder farms and applied multi-criteria analysis to data generated from orthomosaics, to provide a set of sustainability indicators for the farms. Images were acquired from a UAV, with structure from motion (SfM) photogrammetry then used to produce orthomosaics and digital elevation models of the farm areas. Some of the inherent problems using high spatial resolution imagery for land cover classification were overcome by using texture analysis and geographic object-based image analysis (OBIA). Six spatially explicit environmental metrics were developed using multi-criteria analysis and used to generate sustainability indicator layers from the UAV data. The SfM and OBIA approach provided an accurate, high-resolution (~5 cm) image-based reconstruction of smallholder farm landscapes, with an overall classification accuracy of 89%. The multi-criteria analysis highlighted areas with lower sustainability values, which should be considered targets for adoption of sustainable management practices. The results of this work suggest that UAVs are a cost-effective tool for sustainability assessments of oil palm plantations, but there remains the need to plan surveys and image processing workflows carefully. Future work can build on our proposed approach, including the use of additional and/or alternative indicators developed through consultation with the oil palm industry stakeholders, to support certification schemes such as the Roundtable on Sustainable Palm Oil (RSPO).